2014
DOI: 10.1179/2045772313y.0000000192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone mineral loss in patients with chronic traumatic spinal cord injury in Iran

Abstract: Objectives: We described the associations between demographic and injury-related factors on bone mineral density (BMD) of the spine and the hip among adult patients with chronic spinal cord injury (SCI). Design: BMD in spinal and femoral bone sites were assessed. Multivariate analysis was performed to evaluate the relationship between anthropometric and injury-related factors with BMD. Serum level and amount of dietary intake of calcium, phosphor, and 25-hydroxy vitamin D were measured. Setting: A referral ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
(51 reference statements)
1
13
1
Order By: Relevance
“…As a result 41 % of patients were supplemented with this vitamin after their initial evaluation at baseline, with no significant differences between groups (data not shown). Indeed, previous studies have reported a high incidence of vitamin D deficiency (60 %) in SCI patients indicating the need to evaluate and correct this deficiency [28]. Therefore, we cannot totally rule out a possible influence of this supplementation on our results.…”
Section: Discussioncontrasting
confidence: 59%
“…As a result 41 % of patients were supplemented with this vitamin after their initial evaluation at baseline, with no significant differences between groups (data not shown). Indeed, previous studies have reported a high incidence of vitamin D deficiency (60 %) in SCI patients indicating the need to evaluate and correct this deficiency [28]. Therefore, we cannot totally rule out a possible influence of this supplementation on our results.…”
Section: Discussioncontrasting
confidence: 59%
“…The inability to walk and stand can lead to joint contractures, pressure injuries, accelerated osteoporosis, spasticity and shortened life expectancy. [1][2][3] To restore the gait of patients with paraplegia, different types of hip-knee-ankle-foot orthoses (HKAFOs) have been studied. Orthoses equipped with bilateralsided hip joints and hard pelvic supports have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the mild VD deficiency can also contribute to the suboptimal response. VD deficiency is highly prevalent [8] (including in cases with traumatic spinal injury [9]), frequently suboptimally replaced (due to either insufficient doses recommended or decreased compliance) and plays a major role in rehabilitation [9]. This case illustrates the difficulties sometimes raised in appreciating the exact impact of a traumatic event in a patients with severe underlying bone disease.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to its causal role related to the VF, the traumatic injury might have acted also as an aggravating factor of slow response to bisphosphonates. Studies on men with spinal cord injuries proved that with severe posttraumatic neurological damage significant BMD loss is found at the level of the affected lumbar vertebrae [8]. Of course, the mild VD deficiency can also contribute to the suboptimal response.…”
Section: Discussionmentioning
confidence: 99%